Ebastina: obtenção de novas formas cristalinas e caracterização no estado sólido - Ribas, Karla Giacomelli (2015)
Ebastine (EBA) is a second-generation antihistamine with poor water solubility. It is used in the treatment of allergic rhinitis and chronic idiopathic urticaria. For oral administration of drugs, there is a preference for solid dosage forms and the therapeutic efficacy of them is directly related to their solid state. Therefore, it is very important to control these properties during the various phases of the development of drug products. The aim of this work was to evaluate the impact of different crystal habits of EBA on the physico-chemical characteristics of the drug. Four not reported new crystal habits of EBA were obtained through the slow solvent evaporation technique, using different solvents and temperatures. The EBA crystals and raw material were analyzed by solid state techniques including X-ray powder diffraction and single crystal diffraction, differential scanning calorimetry, thermogravimetry, Fourier transform infrared, scanning electron microscopy, intrinsic dissolution rate and powder dissolution. The crystalline structure of EBA was determined through single crystal X-ray diffraction. The powder dissolution results indicated significant difference between dissolution profiles and dissolution efficiency from EBA raw material and the new crystals obtained, suggesting the possible influence of distinct crystal habits on the bioavailability of this drug.